2010
DOI: 10.1177/0047287510362919
|View full text |Cite
|
Sign up to set email alerts
|

Distance Models for New Zealand International Tourists and the Role of Transport Prices

Abstract: We analyse data on the distances travelled using car and air transport modes in New Zealand by a large sample of international tourists from six different countries of origin. We use two-stage hurdle models to relate both the decision to use each mode and the distance travelled by a mode if used to visitor characteristics and prices. In general we find little evidence of price sensitivity for either decision, although older tourists, those with longer stays, and non-tour group travellers may be more price-sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 25 publications
3
22
2
Order By: Relevance
“…The same six-day "increase" in length of stay entails a 19 percentage point reduction in the probability of car transportation being chosen (79 − 60 = 19). This effect of length of stay stands in contrast to Becken and Schiff (2011), who reported that as length of stay increased, so did the probability of a private car being used. In the same manner as for length of stay, larger travel parties also tend more frequently than smaller ones to choose air or public transportation relative to private car.…”
Section: Econometric Resultscontrasting
confidence: 80%
See 3 more Smart Citations
“…The same six-day "increase" in length of stay entails a 19 percentage point reduction in the probability of car transportation being chosen (79 − 60 = 19). This effect of length of stay stands in contrast to Becken and Schiff (2011), who reported that as length of stay increased, so did the probability of a private car being used. In the same manner as for length of stay, larger travel parties also tend more frequently than smaller ones to choose air or public transportation relative to private car.…”
Section: Econometric Resultscontrasting
confidence: 80%
“…This was partly touched upon in Section 2.2 as it is especially relevant for trip-related characteristics. Consider for example the effect of the variable length of stay -where this study's findings are at odds with those of Becken and Schiff (2011). The underlying behavioral model for the present study suggests that prospective tourists first decide on length of stay, and then later on transportation mode.…”
Section: Discussion Limitations and Further Researchcontrasting
confidence: 64%
See 2 more Smart Citations
“…Indeed, an earlier study on tourists' awareness and knowledge of prices of tourist attractions in Queenstown, New Zealand, found that accurate knowledge of prices is very low, and tourists' participation in an activity was more influenced by availability of time or appeal or previous experiences (Lawson, Gnoth, & Paulin, 1995). Recently, a study on the relationship between petrol prices and travel distance (by air or car) in New Zealand found that tourists are not sensitive to petrol prices but that factors such as length of stay, country of origin or travel style influence travel significantly (Becken & Schiff, 2010). Tourists' inelastic behaviour towards transport prices was also found in a study on rental cars in Spain (Palmer-Tous et al, 2007).…”
Section: Discussionmentioning
confidence: 99%